Reviewing Generation Z Adolescent Affective Domain Through Family-Based PAI Assessment - Irhas Sabililhaq; Nursiah; Lia Dwi Utami (al-Afkar, Journal For Islamic Studies, 2024)
This study aims to examine the patterns of PAI assessment through the family in order to review the affective domain of the Z-generation youth. The main problem in this study is the scope of the case of adolescent malpractice and moral degradation, which directly targets the affective realm of the adolescent generation Z. In the midst of the scale of such cases, it is the parents or families who are often ignored and have not been able to cope with it. This research uses a qualitative approach to the type of library study or library research. The research suggests that Z-generation adolescents are a group of generations born as digital natives that are vulnerable to stress and depressed mental endurance. The family as the most important educator should the ideal standard of function, that is, the function of religion, education, social, and salvation. The emotional area assessment pattern for family-based Z-generation adolescents is discussion of stories, events, or problems; monitoring or monitoring of all actions, speeches, and attitudes; appreciation in every goodness; and healthy communication with an open system.